Adapted chester step test can have maximal response characteristics for the assessment of exercise capacity in young women - Vilarinho, Rui (2021)
Chester step test (CST) estimates the exercise capacity through a submaximal response, which can limit its application in the prescription of exercise. This study aimed to assess whether an adaptation of the CST (with a progressive profile) can have maximal response characteristics in young women and compare it to the incremental shuttle walk test (ISWT). Another aim was to determine its within-day test–retest reliability. A cross-sectional study was conducted with 25 women (20.3 ± 1.5 years) who performed the field tests twice on two different days (48 h apart).